James Weldon Johnson's Modern Soundscapes - Morrissette, Noelle (Book collections on Project MUSE., 2013)
This book provides an evocative and meticulously researched study of one of the best known and yet least understood authors of the New Negro Renaissance era. Johnson, familiar to many as an early civil rights leader active in the National Association for the Advancement of Colored People - and an intentionally controversial writer on the subject of the significance of race in America - was one of the most prolific, wide-ranging, and yet elusive authors of twentieth-century African American literature. Johnson realized early in his writing career that he could draw attention to the struggles of African Americans by using unconventional literary methods such as the incorporation of sound into his texts. In this book, a literary critic examines how his literary representation of the extremes of sonic experience - functioning as either cultural violence or creative force - draws attention to the mutual contingencies and the interdependence of American and African American cultures.